Interperasi Kata Qātilū dalam Q.S. Al-Taubah (9): 29 Studi Analisis Kajian Ma‘nā cum Maghzā Sahiron Syamsuddin - Fabrori, Fahri Muhaimin (REVELATIA Jurnal Ilmu al-Qur`an dan Tafsir, 2023)
The verses of the Al-Quran have meanings and purposes related to the history behind the revelation of the verses. The meaning of verses can be explored by various approaches and methods of interpretation. This article examines the word qātilū in Q.S. At-Taubaḥ [9]: 29. The word often has a double meaning so it is understood incorrectly and only the external aspects are discussed. Basically the word qātilū in the Koran means "fight". But in fact the word qātilū in Q.S. At-Tubaḥ [9]: 29 is used as "legal" legitimacy to commit murder. Therefore, this study aims to reveal the meaning of the word qātilū using a descriptive analysis method. The theoretical approach used is the maʻna cum maghza theory initiated by Sahiron Syamsuddin. The process of interpretation in the maʻna cum maghza theory is carried out by: First, paying attention to the meaning of at-tarikhī or the meaning of the language intended by the author. Second, looking for significance (al-ma'na al-tarikhī) is paying attention to the historical context of the studied verse. Third, dynamic phenomenal significance (al-maghza al-mutharrik al-muʻasir). Primary source analysis was carried out by interpreting the word qātilū from various commentaries, the Koran, and supported by secondary sources in the form of relevant books, journals, and articles. The results of this research show that: First, the word qātilū means "fight" namely to the People of the Book, especially the Romans. Second, this verse refers to the permissibility of fighting when Islam is under pressure and threats such as territorial expansion by the people of the book in the Arabian peninsula, disobedience in paying jizya, torture of Muslims, etc. Third, this verse has asbabun nuzul, namely the context of the war with the Romans called Ghazwa al-ʻUra. Fourth, orders to fight are permissible when there are threats, violations of agreements, and rebellion against Islam. When these elements do not occur, fighting/killing other people is prohibited.